Low velocity impact behaviour of pineapple leaf fibre reinforced polylactic acid biocomposites - Sheikh Md Fadzullah, Siti Hajar; Ramli, Siti Nur Rabiatutadawiah; Dhar Malingam, Sivakumar; Mustafa, Zaleha; Mohamad Razali, Nurul Anira Shahidah; Ismail, Ilyas (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
In this study, impact performance of biocomposites fabricated from pineapple leaf fiber reinforced polylactic acid subjected to low-velocity impact loading is presented. The biocomposites were fabricated using compression moulding technique, in which two grades of the polylactic acid matrix materials were considered. Following these, the biocomposites were subjected to dropweight impact testing as per ASTM 3767. In general, it was found that the maximum impact force and total energy absorbed increased linearly with an increase in the impact velocity. Moreover, at velocity of 3 m/s, the PLA 6100D based biocomposites exhibit slightly higher energy absorbed in comparison to those of the PLA 3251D biocomposites, with a value of 16.25 J and 15.74 J, respectively. In addition, more severe damages are observed for the 3251D PLA based biocomposites due to brittle nature of the material, leading to weaker impact properties in comparison to those of the PLA 6100D based biocomposites, as evident in the images of the front and back impact surface.